Paper Tigers and Minotaurs : The Politics of Venezuela's Economic Reforms - Naím, Moises (Book collections on Project MUSE., 1993)
"In rich and illuminating detail, the book analyzes this transformation and the consequences of the new policies that were meant to deal with the deepest economic crisis in Venezuela's history. The crisis was a classic and instructive example for governments everywhere that are undergoing the transition toward markets and away from state intervention. The author examines the initial impact of the reforms on the country's economy and the social situation, including the practical problems and the politics of implementing social "safety nets" to help the poor cope with the harsh burdens of economic adjustments. The book deals forthrightly with the central challenges to economic reform: the military and its reaction to reform and instability; the link between economic liberalization and corruption; the emergence of "media barons" as a political force brandishing unprecedented power; the inability of the government to communicate effectively with the people and build support for the reforms; the effects of the fierce rivalries that broke out among private economic groups; the demise of Carlos Andres Perez, once the most popular and powerful of the country's political leaders." "This engrossing reconstruction and interpretation of the Venezuelan experience is filled with lessons, insights, and deeper questions for all who enter the labyrinth determined to distinguish between the paper tigers and minotaurs that confront economic and political change."--Jacket.